2013
DOI: 10.1016/j.jpedp.2012.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Bone mass in children and adolescents infected with human immunodeficiency virus

Abstract: Objective: To describe bone mineral density (BMD) and bone mineral content (BMC) in children and adolescents infected with the human immunodeficiency virus (HIV), and to compare them with data from the National Health and Nutrition Examination Survey IV (NHANES IV). Method: The study included 48 children and adolescents (7 to 17 years old) infected with HIV through vertical transmission. BMC and BMD were measured by dual energy absorptiometry X-ray, by calculating z-scores based on data from NHANES IV. The inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 27 publications
3
25
1
Order By: Relevance
“…Growth among children and adolescents with HIV/AIDS in the present study was similar to patterns of growth in the general population, with an increase in weight and height with age 26 ; however, these groups were generally below the reference curves 20,21 . This result is in accordance with the literature that shows the influence of ARVT on the bone mass depletion affecting, in its turn, both weight and height 27 .…”
Section: Children and Adolescentssupporting
confidence: 93%
“…Growth among children and adolescents with HIV/AIDS in the present study was similar to patterns of growth in the general population, with an increase in weight and height with age 26 ; however, these groups were generally below the reference curves 20,21 . This result is in accordance with the literature that shows the influence of ARVT on the bone mass depletion affecting, in its turn, both weight and height 27 .…”
Section: Children and Adolescentssupporting
confidence: 93%
“…However, this reduction was not related to calcium intake, but rather to the use of HAART with protease inhibitors. 38 Iron and vitamin A intakes were evaluated in this study, although these intakes are not considered to be accurately estimated by the FFQA. 14 In contrast to evidence that dietary supplements confer benefits in HIV patients, few data are available, and they are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from the NISDI study include a very low mortality rate, dyslipidemia in over a quarter, lower rates of insulin resistance than seen in the United States and Europe, low rates of opportunistic infections but higher than seen in comparable populations in the United States and Europe, and relatively low rates of renal and hepatic disease [83Á87]. Two cross-sectional studies of BMD in Brazil demonstrated that between 17 and 32% of PHIVA studied had low BMD, though larger studies with appropriate comparison groups are clearly needed [88,89]. Data on neurocognitive and mental health problems for PHIVA in this region remain very limited.…”
Section: Latin America and The Caribbean Epidemiology And Long-term Cmentioning
confidence: 99%